Writing revolt an engagement with African nationalism - Ranger, T. O. (Woodbridge Weaver Press, 2013)
This memoir of the years between 1957, when he first went to Southern Rhodesia, and 1967 when he published his first book, is both an intimate record of the African awakening which Ranger witnessed during those ten years, and of the process which led him to write Revolt in Southern Rhodesia. Intended as both history and as historiography, Writing Revolt is also about the ways in which politics and history interacted. The men with whom Ranger discussed Zimbabwean history were the leaders of African nationalism; his seminar papers were sent to prisons and into restricted areas. Both they and he were making political as well as intellectual discoveries. The book also includes a brief account of Ranger's life before he went to Africa.
Includes bibliographical references (pages 191-203) and index.
Keywords: Ranger, T. O